1971
DOI: 10.2466/pms.1971.33.1.307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Task Complexity and Practice on Performance during Acute Alcohol Intoxication

Abstract: A battery of psychological tests was administered to 26 medical smdents in a counterbalanced cross-over design to determine the effects of an acute dose of alcohol on perceptual, perceptual-motor and cognitive capacities. The tests included: temporal acuity (critical flicker fusion threshold), perceptual speed and attention (Stroop), perceptual-motor coordination (Purdue Pegboard) , perceptual-motor speed (simple and choice reaction time), immediate memory (WAIS Digit Span), short-term memory (dichotic stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…First, the pharmacologi cally induced sedative effect was so pronounced that both extraverts and introverts were shifted to an extremely low level of cortical arousal resulting in highly impaired per formance in both groups. This explanation appears to be very unlikely since CFF thresholds were shown not to be affected by blood alcohol concentrations (BAC) up to approximately 60 mg/dl [21,32], Rather, a decrement in CFF performance is unlikely to appear until a BAC of at least 70 mg/dl is reached [33,34], These results on the relationship between BAC and CFF performance suggest that a BAC of approximately 70 mg/dl represents the low er limit for the occurrence of alcohol-induced sedative effects on CFF. These considerations are in agreement with the decrease in CFF threshold values observed in the present study at a mean BAC of approximately 75 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…First, the pharmacologi cally induced sedative effect was so pronounced that both extraverts and introverts were shifted to an extremely low level of cortical arousal resulting in highly impaired per formance in both groups. This explanation appears to be very unlikely since CFF thresholds were shown not to be affected by blood alcohol concentrations (BAC) up to approximately 60 mg/dl [21,32], Rather, a decrement in CFF performance is unlikely to appear until a BAC of at least 70 mg/dl is reached [33,34], These results on the relationship between BAC and CFF performance suggest that a BAC of approximately 70 mg/dl represents the low er limit for the occurrence of alcohol-induced sedative effects on CFF. These considerations are in agreement with the decrease in CFF threshold values observed in the present study at a mean BAC of approximately 75 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of whether the impairment in temporal acuity has any significant effect on driving skill, the available data suggest that the temporal acuity of the visual system is slightly impaired by high BAC's. One possible explanation for the conflicting results found by Lewis et al (1969) may be that practiced subjects were used in that experiment, and practice is known to mitigate the effects of alcohol (Tarter, Jones, Simpson, & Vega, 1971) and to change the criteria for psychophysical judgments. Intensive attention and viqilance.…”
Section: Dynamic Visual Acuitymentioning
confidence: 49%
“…• glare resistance and recovery--the ability to tolerate an intense light source and still obtain useful information from the surrounding field and the ability to recover from the effects of glare (Mortimer, 1963;Newman & Fletcher, 1941); and • temporal acuity of the visual system--usually measured by the critical flicker fusion (CFF), the slowest rate of flicker at which an intermittent light source is perceived as continuous (Simonson & Enzer, 1941;Tarter, Jones, Simpson & Vega, 1971). Burg (1970), in a comparison of three-year driving records of over 14,000 drivers with visual function, concluded that dynamic visual acuity showed the strongest correlation with driving record and static visual acuity; visual field and glare recovery showed some -17-relation.…”
Section: Sensory Processesmentioning
confidence: 99%
“…For example, it has been demonstrated that alcohol can impair perceptual and cognitive functioning (e.g., Tarter et al, 1971). Alcohol intoxication, coupled with the computer tasks participants completed while the cues were being presented during the conditioning sessions, may have impeded conditioning with our visual stimulus.…”
Section: Discussionmentioning
confidence: 99%